1997
DOI: 10.4141/a96-133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection for lower backfat, and increased levels of dietary amino acids to digestible energy on growth performance, carcass merit and meat quality in boars, gilts, and barrows

Abstract: Effects of selection for lower backfat, and increased levels of dietary amino acids to digestible energy on growth performance, carcass merit and meat quality in boars, gilts and barrows. Can. J. Anim. Sci. 77: [487][488][489][490][491][492][493][494][495][496]. Two experiments were conducted, using a total of 288 crossbred boars, gilts and barrows from the progeny of two Yorkshire sow lines, one kept as control, and the other selected for lower backfat thickness and increased growth rate for six generations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
17
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
(20 reference statements)
8
17
0
3
Order By: Relevance
“…O mesmo foi observado por Grandhi & Cliplef (1997) e Souza Filho et al (1999, que não constataram efeito do nível de lisina sobre a AOL, sobre a espessura de toucinho no P 2 (ETP 2 ) e o rendimento de carne magra (RCM), em suínos com alto potencial genético para deposição de carne magra, abatidos aos 130 e 105 kg, respectivamente.…”
Section: Feed:lean Ratiounclassified
See 1 more Smart Citation
“…O mesmo foi observado por Grandhi & Cliplef (1997) e Souza Filho et al (1999, que não constataram efeito do nível de lisina sobre a AOL, sobre a espessura de toucinho no P 2 (ETP 2 ) e o rendimento de carne magra (RCM), em suínos com alto potencial genético para deposição de carne magra, abatidos aos 130 e 105 kg, respectivamente.…”
Section: Feed:lean Ratiounclassified
“…Apesar da coerência entre os dados de carcaça nos trabalhos, o valor médio de 40 cm 2 de AOL, encontrado neste estudo foi superior aos valores médios de 37,2, 38,6 e 31,3 cm 2 , respectivamente observados por Friesen et al (1995), Hahn et al (1995) e Grandhi & Cliplef (1997); e similar ao valor médio de 40,1 cm 2 obtido por Gonçalves et al (1999).…”
Section: Feed:lean Ratiounclassified
“…The selection for high growth rate and low back fat thickness or muscularity in pigs has affected meat quality (Grandhi and Cliplef 1997, Knapp et al 1997, Sonesson et al 1998. A comparison of the modern intensively selected pig and the unselected line representing the pig population existing 20 years ago (Oksbjerg et al 2000, Tribout et al 2003, and selection experiments (Sonesson et al 1998, Cameron et al 1999) have shown some deterioration in water holding capacity, meat colour, tenderness and pH.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs were slaughtered at 105.2 ± 0.3 kg body weight at a local abattoir for carcass quality evaluation. The procedures for measuring carcass index and dressing percent were the same as those reported by Grandhi and Cliplef (1997). The carcass index was determined within 1 h of postmortem, and the dressing percent was calculated using the cold carcass weight after keeping carcasses in a cooler for 24 h. All pigs used in this experiment were housed and managed according to the guidelines of the Canadian Council on Animal Care (1993), and the animal use protocol (Animal utilisation assessment form # 97-04) was approved by the Brandon Research Centre Animal Care Committee.…”
mentioning
confidence: 99%
“…The metabolism crates used during the finisher period had perforated plastic (Tenderfoot) flooring below which was a removable tray with a plastic lining to collect faeces. The sample collection procedures were similar to those described by Grandhi (1994) and Grandhi and Cliplef (1997). Urine was collected into covered plastic pails containing 60 mL of 38% HCl.…”
mentioning
confidence: 99%